Use of Combined MSAP and NGS Techniques to Identify Differentially Methylated Regions in Somaclones: A Case Study of Two Stable Somatic Wheat Mutants - Baránek, Miroslav; Čechová, Jana; Kovacs, Tamas; Eichmeier, Aleš; Wang, Shunli; Raddová, Jana; Nečas, Tomáš; Ye, Xingguo (PLoS One, 2016)
The appearance of somaclonal variability induced by in vitro cultivation is relatively frequent and can, in some cases, provide a valuable source of new genetic variation for crop improvement. The cause of this phenomenon remains unknown; however, there are a number of reports suggesting that epigenetics, including DNA methylations, are an important factor. In addition to the non-heritable DNA methylation changes caused by transient and reversible stress-responsive gene regulation, recent evidence supports the existence of mitotically and meiotically inherited changes. The induction of phenotypes via stable DNA methylation changes has occasionally great economical value; however, very little is known about the genetic or molecular basis of these phenotypes. We used a novel approach consisting of a standard MSAP analysis followed by deep amplicon sequencing to better understand this phenomenon. Our models included two wheat genotypes, and their somaclones induced using in vitro cultivation with a changed heritable phenotype (shortened stem height and silenced high molecular weight glutenin). Using this novel procedure, we obtained information on the dissimilarity of DNA methylation landscapes between the standard cultivar and its respective somaclones, and we extracted the sequences and genome regions that were differentially methylated between subjects. Transposable elements were identified as the most likely factor for producing changes in somaclone properties. In summary, the novel approach of combining MSAP and NGS is relatively easy and widely applicable, which is a rather unique feature compared with the currently available techniques in the epigenetics field.
Keywords: Triticum; DNA Methylation; DNA rostlinná; DNA, Plant; Mutation; mutace; transpozibilní elementy DNA; pšenice; DNA Transposable Elements; polymorfismus genetický; metylace DNA; vysoce účinné nukleotidové sekvenování; High-Throughput Nucleotide Sequencing; Polymorphism, Genetic